Kentucky Illustrated : The First Hundred Years - Schmidt, Martin F., 1918- (Book collections on Project MUSE., 2015)
Kentucky Illustrated brings together a substantial portion of the pictorial scenes published during Kentucky's first century, many of them rare prints reproduced here for the first time since their original publication. From the frontier days of Daniel and Squire Boone to the rise of the railroads that opened the state to visitors who toured its landmarks and bathed in its springs, more than two hundred views offer a picture of Kentucky's growth and civilization. Until the 1890s, Kentucky was sketched in the words of adventurers, travelers, and journalists, but all most Americans knew of the f.